Multi-View Retrieval Of Software Design Specifications Using Similarity Assessment Approach - Adamu, Alhassan (2017)
This study examines how software designs that are modelled using Unified Modelling Language (UML) can be reused. A notable understanding is that UML model software systems from different but related perspectives. The main issues that arise when reusing these designs is how the similarity between the UML artifacts can be computed from multiple perspectives. However, there is no definitive approach that computes the similarity between the UML artifacts across the views while maintaining the consistency across these views. Consequently, this thesis proposes a new similarity assessment approach that facilitates the computation of similarity between UML artifacts from multiple perspectives.